Effectiveness of a stimulation program in the immediate auditory memory, reading comprehension and problem solving in children of second grade - Yaringaño L., Juan (2014)
The research studies the effect of a stimulation program in the immediate auditory memory, reading comprehension and problem solving in a group of second graders primary education in their implementation the experimental method was employed with a quasi- experimental design with group control. We worked with 52 children of both sexes, second grade, who formed two groups one experimental and one control . Subjects were assessed with the Test of Auditory Immediate Memory (MAI), the Test of Linguistic complexity Progressive (CLP ) and the Test of Mathematical Behavior before and after application of the stimulation program. The experimental group underwent 16 sessions of a stimulation program. The results showed that the program was effective in the immediate auditory memory and logical memory component, as the score of the experimental group in the post test exceeded the control group. Similarly, the experimental group outperformed the control group in reading comprehension scores. Finally no significant differences between experimental and control groups were found in problem solving.